PKM Analysis of Working Capital and Return to Main Livestock Business B2 Likupang District, Minahasa Utara - Joubert B. Maramis; Victor P.K. Lengkong; Jantje L. Sepang; Jeffrey L. Tampenawas (AIBPM Publisher, 2019)
In the main coastal area in Likupang District, there are still many B2 farmers who release their livestock freely (without pens). Farmers who do not breed B2 livestock, the majority of the reason is that they are less able to buy fodder regularly. According to them, if it is grounded it will require a very large cost to buy food, whereas if left (released) B2 will find its own food so that the owner does not spend high feed costs. Also, the ability to calculate working capital and analyze home a very important point in conducting livestock business B2. And the results of observations and interviews with B2 livestock owners, concluded that their financial abilities were mostly inadequate. Constraints faced by B2 breeders in Likupang District are the value of entrepreneurship that indeed requires a long term to change, the traditional habits of farmer management are still strong, consistency and continuity of assistance is still lacking, Tolerance of surrounding communities to B2 animals released is still quite high (tolerant) However, there is still no professional B2 livestock group, the cost for cages is high and B2 animal feed costs are high. After counseling, there is an increase in B2 farmers' understanding of the importance of working capital and return home. B2 breeders are motivated (temporarily) to want to plant their livestock. Keywords: working capital, return home, breeders, pigs, northern Minahasa